EFEKTIVITAS RUBRIK MULTILITERASI DALAM MENGUKUR KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Maya Eka Purwanti; Intan Sari Rufiana; Sri Rahayuningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the limited effectiveness of conventional assessment practices in measuring elementary students’ critical thinking skills, particularly in the context of 21st-century learning demands. The research aims to analyze the effectiveness of multiliteracy-based rubrics in assessing and improving students’ critical thinking skills, including interpretation, analysis, evaluation, and inference. This study employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest model. The sample consisted of elementary school students selected through purposive sampling. Data were collected through critical thinking tests and analyzed using the N-Gain formula to determine the level of improvement. The results indicated a significant increase across all indicators: interpretation (N-Gain = 0.7), analysis (0.716), evaluation (0.695), and inference (1.455). These findings demonstrate that multiliteracy rubrics are effective not only as assessment tools but also as instruments to enhance higher-order thinking skills. However, the unusually high N-Gain in inference suggests the need for further validation of scoring procedures. Overall, the integration of multiliteracy rubrics contributes positively to structured, authentic, and meaningful assessment practices in elementary education.